Etanercept‐Methotrexate Combination Therapy Initiators Have Greater Adherence and Persistence Than Triple Therapy Initiators With Rheumatoid Arthritis. Issue 12 (December 2015) - Bonafede, Machaon; Johnson, Barbara H.; Tang, Derek H.; Shah, Neel; Harrison, David J.; Collier, David H.
Abstract : Objective: To estimate adherence and persistence with etanercept plus methotrexate (ETN‐MTX) combination therapy and MTX, hydroxychloroquine, and sulfasalazine triple therapy at 1 year following treatment initiation in adults with rheumatoid arthritis (RA). Methods: This retrospective analysis used data from the Truven Health MarketScan Commercial and Medicare Supplemental databases from January 2009 to July 2013. Adherence was defined as having percentage of days covered >80% for all drugs within each regimen. Persistence was defined as no treatment gap >45 days for any drug and no addition or switching to other disease‐modifying antirheumatic drugs. Multiple logistic regression models were employed in the analyses to control for potential confounders. Results: A total of 3, 724 ETN‐MTX patients and 818 triple therapy patients were eligible. At 1 year, 27.9% who were taking ETN‐MTX and 18.2% using triple therapy were adherent to all agents in their regimen ( P < 0.0001), and 29.4% who were taking ETN‐MTX and 23.2% using triple therapy were persistent ( P < 0.001). After adjusting for confounders, ETN‐MTX patients had significantly greater odds of being adherent (odds ratio [OR] 1.79, 95% confidence interval [95% CI] 1.47–2.17) and persistent (OR 1.45, 95% CI 1.20–1.72) compared with patients using triple therapy. Conclusion: Patients with RA initiating treatment with ETN‐MTX combination therapy demonstrated greater adherence and persistence at 1 year than patients initiating triple therapy.